The pioneer burial : a high-status Anglian warrior burial from Wollaston Northamptonshire - Meadows, Ian, (Archaeopress archaeology., 2019)
Excavations at Wollaston Quarry, near Wellingborough, uncovered a single late 7th century grave, the Pioneer burial. The burial contained artefacts indicative of very high status, with the early to middle Saxon helmet being at the time only the fourth to have been recovered from a burial in England.